The role of the conditionality of EU membership in migrant criminalization in the Western Balkans - Kogovšek Šalamon, Neža (Dve domovini, 2019)
The EU's responses to migration challenges exceed the territory of its member states. Through externalization of border control they spill over into the countries of the Western Balkans (WB), which is crossed by one of the most important migration routes from the Middle East and Africa to the EU. While the WB countries show indifference towards migrants and consider them an "EU problem", the latter conditions European integration with the establishment of migration management structures similar to those in the EU. The transposition of the EU acquis also increases the criminalization of migrants, which highlights the problematic role of the EU and national legislators in WB in relation to the fundamental rights of migrants.
Keywords: človekove pravice; detention; European Union; Evropska unija; kazensko pravo; krimigracije; kriminalizacija; migracije; migracijska politika; migrant criminalization; migration; pridržanje; Western Balkans; Zahodni Balkan